Regional telejournalism in the interior of Rio Grande do Sul: the presence of RBS TV and the Jornal do Almoço - Marques, Paulo (2023)
In recent years, television stations in Rio Grande do Sul have gone through restructuring processes that have contributed to the extinction or reduction of regional news spaces. The broadcaster RBS TV still meets, in a way, this demand, even if, gradually, it has been reducing its operations in the interior of Rio Grande do Sul. The study aims to problematize the importance of regional journalism, especially television, within the state of Rio Grande do Sul. The analysis was focused on the RBS TV station, specifically on the Jornal do Almoço program. Through the observation methodology (GIL, 2008), six editions of the television news were analyzed during the period of one week. The observational method was aimed at verifying the time allocated to each region in relation to the total time of the television news and which subjects were dealt with by each regional segment. In addition, considerations were presented on the observations of the editions analyzed. As a result, it could be seen that, over the years, the RBS TV station is gradually reducing access to information for communities in the interior of Rio Grande do Sul.